Development of an interactive PowerPoint to instill a deeper understanding of polyhedron concepts in mathematics class - Nur Izzati; Nurul Wahyuni; Bony Irawan (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
Mathematics is generally considered a complex subject by the majority of students in Indonesia. Students tend to rely on simple learning strategies such as memorizing formulas. This perpetual trend distance our students from deeper mathematical understandings such as concept application. In this study, we develop an interactive learning media based on Microsoft PowerPoint to instill a deep conceptual understanding of polyhedrons in class VIII students. This Research and Development study follows the 4D development model with a limited dissemination phase. The research data was collected through validation techniques by expert validators to measure the feasibility level of learning media. The instruments used in the research were interview sheets, observation sheets, learning style tests, media validation sheets, language validation sheets, and material validation sheets. The data analysis technique uses the Method of Summated Ratings, then the eligibility percentage for the developed media is calculated. The results showed that the eligibility percentage for media experts was 92%, material experts 96%, and linguists 90%. The average percentage of the three assessments corresponds to the “very valid” category. In conclusion, the media developed is very feasible for its intended purpose.